The direct and indirect impacts of liberal immigration policies on the United States' economy - Geiguen Shin (Economics: The Open-Access, Open-Assessment E-Journal, 2020)
Many studies have suggested that stringent labor protections and higher labor costs can limit foreign direct investment (FDI) in host countries. This would imply that the decisions of foreign firms are sensitive to the degree of flexibility in the labor market in the U.S. The U.S. has a steady stream of immigration, which has preserved the stability of the labor supply for the U.S. market. This makes the U.S. a good test case for the relationship between immigration and FDI because it is not only the largest host for FDI but also has the largest immigrant population in the world in absolute terms and is experiencing a significant reduction in labor supply and an increase in the minimum cost of labor. Utilizing a time-series analysis of data from 1970 to 2016, this study suggests that expansive immigration policies directly increase FDI inflows in the U.S. and indirectly increase FDI inflows by lowering labor costs and securing a stable supply of labor.
http://dx.doi.org/10.7910/DVN/0V82MQ
Keywords: F16; J15; 330; foreign direct investment; immigration policy; labor cost